Determinación de la calidad mecánica, fisicoquímica y microbiológica de la carne bovina que se expende en Chone - Zambrano Chavarría, Nely Yomaira (2025)
This research determined the mechanical, physicochemical, and microbiological quality of beef sold in the central area of the Chone canton. Descriptive and analytical methods were used, including a checklist to assess sanitary conditions, texture profile analysis to determine hardness, elasticity, and cohesiveness, potentiometric and volumetric methods to measure pH and acidity, and microbiological cultures to identify microbial load. The checklist results indicated that only 47% of butcher shops meet the established sanitary requirements, with deficiencies in infrastructure and sales areas. Meat samples showed a pH higher than 6.5 in several butcher shops, indicating DFD meat (dark, firm, and dry), and an acidity ranging from 0.05% to 0.11%. No significant amounts of organochlorine or organophosphate pesticide residues were detected. However, samples presented a high microbial load, and Salmonella was detected in at least one sample from each butcher shop, failing to meet the microbiological standards established by NTE INEN 1338:2016. In conclusion, the beef sold in Chone does not meet the necessary quality standards, highlighting the need to improve handling and marketing practices to ensure food safety.